1997
DOI: 10.1021/bi9703756
|View full text |Cite
|
Sign up to set email alerts
|

A New Pathway for Transmembrane Electron Transfer in Photosynthetic Reaction Centers of Rhodobacter sphaeroides Not Involving the Excited Special Pair

Abstract: It is generally accepted that electron transfer in bacterial photosynthesis is driven by the first singlet excited state of a special pair of bacteriochlorophylls (P*). We have examined the first steps of electron transfer in a mutant of the Rhodobacter sphaeroides reaction center in which charge separation from P* is dramatically slowed down. The results provide for the first time clear evidence that excitation of the monomeric bacteriochlorophyll in the active branch of the reaction center (B(A)) drives ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 30 publications
12
118
4
Order By: Relevance
“…In line with the multimer model, in which the similarity in magnitude of the exciton coupling and energetic disorder results in exciton states delocalized over several cofactors (14,37), it is reasonable to consider that depending on protein conformation, distinct exciton states are present in the system. Each of these leads to a different pathway of charge separation, which has also been demonstrated for the bacterial reaction center (7)(8)(9). At this point a question arises: is the protein actively involved in the determination of a pathway or is this determination only dependent on random static disorder?…”
Section: Discussionmentioning
confidence: 96%
“…In line with the multimer model, in which the similarity in magnitude of the exciton coupling and energetic disorder results in exciton states delocalized over several cofactors (14,37), it is reasonable to consider that depending on protein conformation, distinct exciton states are present in the system. Each of these leads to a different pathway of charge separation, which has also been demonstrated for the bacterial reaction center (7)(8)(9). At this point a question arises: is the protein actively involved in the determination of a pathway or is this determination only dependent on random static disorder?…”
Section: Discussionmentioning
confidence: 96%
“…Global analysis was performed as described in ref. 18 with the addition that the wavelength dependence of time-zero caused by group velocity dispersion (GVD) was taken into account. To achieve this, the rise and decay of the optical Kerr signal in CS 2 measured over the different wavelength windows was analyzed with a third-order polynomial function to describe the variation of time zero of the IRF.…”
Section: Methodsmentioning
confidence: 99%
“…This finding implied that an ultrafast and efficient alternative pathway for charge separation driven by monomeric pigments must exist. For the YM210W and YM210L mutants, in which the rate of P*-driven charge separation is slowed down to hundreds of ps, the presence of this alternative pathway for primary charge separation could be clearly resolved in pump-probe experiments (17,18). The charge-separated states formed from B A * in 200 fs were interpreted as P ϩ B A Ϫ and B A ϩ H A Ϫ , which in turn evolved to P ϩ H A Ϫ in a few ps.…”
mentioning
confidence: 99%
“…These observations have led a number of authors to suggest that primary charge separation might occur differently in PSII, potentially initiated by excitation of B A rather than P A /P B . A number of groups have shown in bacterial reaction centers that it is possible to observe, under certain conditions, the formation of radical pair states upon direct excitation of B A (69,128,130,142). Dekker & van Grondelle (24) and Rutherford and coworkers (98,99) have suggested that in PSII the lack of spectral differentiation and the orientation of 3 P, respectively, might be consistent with a contribution of B * A to primary radical formation.…”
Section: Pheomentioning
confidence: 99%